Modeling of reliability of logistic systems of urban freight transportation taking into account street congestion - Vojtov, Viktor; Kutiya, Olesya; Berezhnaja, Natalija; Karnaukh, Mykola; Bilyaeva, Oksana (Eastern-European Journal of Enterprise Technologies, 2019)
Mathematical formulation of the problem of forming urban freight transportation is performed. The structure of the system information model is developed, which takes into account material, energy and information flows. Mathematical expressions for calculating the criterion for choosing rational routes ‒ route quality factor are presented. The criterion takes into account the capabilities of the logistics center (information content), cargo weight, congestion (traffic jams), transportation distance and actual delivery time. A distinguishing feature is that it is determined online and takes into account the congestion dynamics of routes during a work shift. The dynamic model of delays in decision making in the logistics chains of urban freight transportation is developed. The model allows calculating the processing time of transportation requests and transportation time itself. It is shown that the total time of freight delivery consists of the travelling time of the vehicle, taking into account route resistance and delay time in all logistic chains of the system. The mathematical model is developed for assessing the reliability of urban freight transportation, taking into account street congestion. The model operates online and allows determining the parameters of the transport process, including traffic jams on city streets. The reliability criterion of the logistics system of urban freight transportation ‒ reliability coefficient is proposed. The criterion takes into account the travelling time of the vehicle and the delay time of receipt of transportation requests at the logistics center, and the time of delays at the transport company. It is shown that in the absence of delays in logistics chains, the reliability coefficient is equal to unity, and if there is a delay, the reliability coefficient is less than unity. The physical significance of the reliability criterion is determined. It is the share of non-fulfillment of transportation requests on time.